Meningkatkan Potensi Desa Simpang Tiga Melalui E-Commerce Produk Unggulan Melalui Pendekatan Asset Based Community Development - Fransiskus Panca Juniawan; Aurellia Valentcia; Dwita Putri Septiani; Chaca Ananda Putri; Ismail Mazidii; Frizki Amando Pasha (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
Simpang Tiga Village has the potential for superior products such as pelawan mushrooms, pelawan honey, and red rice with high economic value, but product marketing is still carried out conventionally so that market reach is limited and has an impact on community income that is not optimal. In addition, the low digital literacy of the community and the absence of digital-based marketing media are obstacles in developing the village economy. This community service activity aims to increase the economic potential of Simpang Tiga Village through the implementation of an e-commerce website for the village's superior products using the Asset Based Community Development (ABCD) approach. The implementation method is carried out through five ABCD stages, namely identifying village assets, strengthening village assets, mapping and developing networks, developing action plans, and implementing and evaluating activities. Activities carried out include developing an e-commerce website, training on website usage, and digital marketing assistance to the community and BUMDes managers. The results of the activity show that the e-commerce website is able to help promote the village's superior products digitally and increase community understanding of digital marketing. Based on the results of the evaluation of 23 participants, the average understanding score increased from 48.69 in the pre-test to 86.00 in the post-test with a percentage increase of 74,57%. This activity demonstrates that the ABCD approach is capable of supporting the development of a village economy based on local assets through the participatory and sustainable use of digital technology